Does a District-Vote Matter for the Behavior of Politicians? A Textual Analysis of Parliamentary Speeches - Andreas Born; Aljoscha Janssen (Research Institute of Industrial Economics (IFN), 2020)
In most democracies, members of parliament are either elected over a party list or by a district. We use a discontinuity in the German parliamentary system to investigate the causal effect of a district-election on an MP's conformity with her party-line. A district-election does not affect roll call voting behavior causally, possibly due to overall high adherence to party voting. Analyzing the parliamentary speeches of each MP allows us to overcome the high party discipline with regard to parliamentary voting. Using textual analysis and machine learning techniques, we create two measures of closeness of an MP's speeches to her party. We find that district-elected members of parliament do not differ, in terms of speeches, from those of their party-peers who have been elected through closed party lists. However, both speeches and voting correlate with district characteristics suggesting that district-elections allow districts to select more similar politicians.
Keywords: D72; 330; Party-line; Textual Analysis; Regression Discontinuity; Parliamentary Speeches; Voting